Transcriptomic analysis of Rhipicephalus microplus hemocytes from female ticks infected with Babesia bovis or Babesia bigemina - Rubikah Vimonish; Janaina Capelli-Peixoto; Wendell Johnson; Lowell Kappmeyer; Perot Saelao; Naomi Taus; Chungwon Chung; Massaro Ueti (Parasites & Vectors)
Abstract Background Tick hemolymph is a sterile fluid that carries nutrients to maintain tick health. The hemolymph creates a hostile environment for invaders including the destruction of microorganisms by its circulating hemocytes. However, Babesia parasites escape and disseminate to other organs through the hemolymph to continue their transmission life cycle. Still, it is unknown how tick hemocytes respond to B. bovis or B. bigemina infection. In this study, we conducted a transcriptomic analysis of hemocytes from female Rhipicephalus microplus ticks infected with Babesia parasites to understand how gene expression changes during parasite infection. Methods During Babesia acute infection, female R. microplus ticks were fed on bovines to acquire parasites. Engorged females were collected and incubated to develop Babesia kinetes in tick hemolymph. The hemolymph was examined to identify ticks that were highly infected with Babesia kinetes. Hemocyte cells were collected from replete female ticks infected with Babesia bovis or Babesia bigemina to perform high-throughput RNA-sequencing (RNA-Seq) analysis. Results This study identified major changes in the gene profile of tick hemocytes during Babesia infection. The main groups of hemocyte genes that were altered during Babesia infection were associated with metabolism, immunity, and cytoskeletal rearrangement. Upregulated genes were mainly involved in defense mechanisms, while downregulated genes were related to cell proliferation and apoptosis. However, the expression of hemocyte genes varied among Babesia species’ infections, and it reflected the changes that occurred in the tick’s physiology, including growth, reproduction, and skeletal muscle development. Conclusions The differential gene expression of R. microplus hemocytes revealed that genes highly regulated upon Babesia infection were related to metabolism, tick immunity, cell growth, apoptosis, development, metabolism, and reproduction. Additional research is necessary to further define the genes that exhibited varying expression levels in hemocytes during the infection. The findings of this study will enhance our understanding on how Babesia parasites survive in the hostile environment of ticks and perpetuate their transmission cycle, ultimately contributing to the spread of bovine babesiosis. Graphical Abstract